Dietary effects of Sideritis scardica “mountain tea” on human in vivo activities of xenobiotic metabolizing enzymes in healthy subjects - Begas, Elias; Kilindris, Thomas; Kouvaras, Evangelos; Tsioutsioumi, Agoritsa; Kouretas, Demetrios; Asprodini, Eftihia K. (Food and chemical toxicology, 2018)
Sideritis scardica(S. scardica) is an endemic plant of the Balkan Peninsula traditionally used as herbal tea for inflammation and gastric disorders. Aqueous herbal extracts may affect the activity of Phase I and II enzymes involved in xenobiotic metabolism. The purpose of the present study was to determine whether S. scardica decoction alters the activity of CYP1A2, CYP2A6, XO, NAT2 and UGT1A1/1A6 enzymes in humans. Fourteen healthy subjects consumed S. scardica decoction for six days. Enzyme phenotyping was assessed in saliva and urine using caffeine and paracetamol metabolite ratios as follows: CYP1A2: 17X/137X (saliva) and (AFMU+1U+1X)/17U, CYP2A6: 17U/(17U + 17X), XO: 1U/(1U+1X), NAT2: AFMU/(AFMU+1U+1X) and UGT1A1/1A6: glucuronidated/total paracetamol (urine). After S. scardica intake, CYP1A2 index was reduced by ∼16% and ∼8% in saliva (before: 0.54 ± 0.18, after: 0.46 ± 0.09; p = 0.08) and urine (before: 3.59 ± 0.52, after: 3.67 ± 0.78; p = 0.12), respectively. CYP2A6 index was significantly reduced only in males (before: 0.76 ± 0.08, after: 0.67 ± 0.07; p = 0.004), suggesting sexual dimorphism in CYP2A6 inhibition. There was no effect of Sideritis scardica treatment on XO, NAT2 or UGT1A1/1A6 indices. Usual consumption of the aerial parts of S. scardica decoction is unlikely to result in herb-drug interactions involving the enzymes studied, with the exception of potential herb-CYP2A6 substrate interaction in males. •Herb extracts may affect the activity of enzymes involved in xenobiotic metabolism.•The effect of S. scardica decoction was examined on the activity of xenobiotic metabolizing enzymes in healthy volunteers.•CYP1A2, XO, NAT2 or UGT1A1/1A6 activities are not significantly altered after 6-day Sidertis scardica consumption.•CYP2A6 activity is significantly reduced in male volunteers following S.scardica consumption.